Implicações nacionais da integração regional: as eleições diretas do Parlamento do Mercosul - Mariano, Karina Lilia Pasquariello [UNESP]; Luciano, Bruno Theodoro (My University, 2012)
The process of institutionalization of MERCOSUR in recent years has increased the weight of regional integration in the internal policies of the Member States. In the Brazilian case, the bill that regulates direct elections for the MERCOSUR Parliament (Parlasul) in 2014 is an example of this influence, because it includes aspects that are related to discussions on the reform of the Brazilian political system, generating intense debate and controversy within the Congress. This article discusses the possible impacts that its adoption will have on the conduct of political reform in Brazil, on the assumption that this project represents a spillover of political reform for Brazilian regional plan. We assume that its approval can become a test of political reform planned to perform at the regional changes still under discussion in the brazilian legislature. We remind that the decision and approval of the criteria for the Parlasul direct elections is a competence of each Member-State.

O processo de institucionalização do MERCOSUL verificado nos últimos anos aumentou o peso da integração regional nas políticas internas dos Estados-membros. No caso brasileiro, o projeto de lei que regulamenta as eleições diretas para o Parlamento do MERCOSUL (Parlasul) em 2014 é um exemplo dessa influência, porque inclui aspectos que estão relacionados às discussões acerca da reforma do sistema político brasileiro, tema gerador de intenso debate e polêmica dentro do Congresso Nacional. Este artigo discute os possíveis impactos que a sua aprovação terá na condução da reforma política no Brasil, partindo da hipótese de que o referido projeto representa um transbordamento da reforma política brasileira para o plano regional. Supomos que sua aprovação pode se tornar um ensaio da reforma política planejada, ao executar no plano regional mudanças ainda em discussão no legislativo brasileiro. Lembramos que a decisão e aprovação dos critérios para realização das eleições diretas do Parlasul é de competência de cada Estado-membro.
National implications of regional integration: direct elections of MERCOSUR Parliament
Keywords: Regional integration; Direct elections; MERCOSUR Parliament; Integração regional; Eleições; Parlasul; Congresso Nacional